A Theoretical Analysis of Integral Theory and the Participatory Paradigm through the Lens of Otherness - Fernandez-Borsot, Gabriel (California Institute of Integral Studies, 2017)
This dissertation aims to fulfill two objectives. First, to establish a critical perspective of analysis based on the construct of otherness. I term this perspective the “Lens of Otherness” (LoO) and it consists in analyzing the ways otherness is integrated in a theory. A significant part of this work is devoted to substantiate it and provide a theoretical and methodological foundation for it. The second goal is to apply the LoO to two major transpersonal theories, integral theory and the participatory paradigm. The application of the LoO to these two transpersonal theories brings their problematic aspects to the fore. The overall argument is broken down into several steps. The first step consists of compiling a significant number of critiques of transpersonalism that point to a common problem: an inadequate treatment of otherness. Next, the study shows that otherness is a fundamental aspect for both the human being and the universe at large. In order to demonstrate this, a model for otherness in transpersonal studies is created. This model contains five modalities of otherness with increasing significance. Once having shown the relevance of otherness, a critical perspective of analysis based on otherness, the LoO, is formed. A method to guide the application of this critical perspective to transpersonal theories is provided as well. Then the LoO is applied to exemplars of the two major orientations in transpersonal theories, integral theory and the participatory paradigm. The main conclusion of this analysis is that while integral theory presents many flaws from the perspective of otherness, otherness is a foundational constituent of the participatory paradigm. Many other critiques are developed that are of paramount relevance for transpersonal studies. This work will be of interest to all scholars interested in transpersonal studies, and more generally to spiritual seekers who are attracted to the ideas and principles of transpersonal theories.